Power inverter for high speed starter/generator in aircraft applications - Geng, Shen (2016)
Over the recent years, advances in power electronics and electrical machines have permitted the use of the electric starter/generator directly coupled to the shaft of the gas turbine engine driven by the aerospace starter/generator to a self-sustaining speed in the start mode and later converter the mechanical energy of the turbine into electricity in the generator mode. The starter/generator have the following features. Its rated speed can reach as high as the speed of 50000 revolutions per minutes. The rated frequency of supply voltage can be as high as 1000 Hertz. Typically it has relatively few turns on the stator windings so that the currents can build rapidly under high speed operations. However, when the number of turns are reduced, the stator inductance becomes small so that the machine is sensitive to the harmonic distortion of the supply voltage of the machine. Due to the constrains of switching frequency of the inverter, the inverter will induce large current ripples for this high speed motor compared with conventional motor drive with the rated frequency of 50 Hertz. Increased current ripple leads to a high level of Total Harmonic Distortion (THD) in the stator current waveform. Therefore, the aim of this project is to implement a control system for the high speed starter/generator.